2011
DOI: 10.1093/tropej/fmr035
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Determinants of Undernutrition and its Trends among Pre-School Tribal Children of Maharashtra State, India

Abstract: A community-based cross-sectional study carried out in tribal areas of Maharashtra covering 1751 pre-school children to assess nutritional status. Nutritional status was assessed using new WHO Growth Standards. Household wealth index was constructed using principle component analysis. The prevalence of underweight, stunting and wasting was 64, 61 and 29%, respectively. There was a significant (p < 0.05) reduction in the prevalence of underweight and stunting over two time periods (1999 and 2008). Logistic regr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
27
4
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 10 publications
10
27
4
1
Order By: Relevance
“…The study found that the prevalence of underweight was about 64%, and that the prevalence of underweight was 1.7 times higher in children of illiterate women. 18 The present study also supports previous studies that maternal educational status is a very important determinant for nutritional status of children.…”
Section: Factors Associated With Underweightsupporting
confidence: 92%
See 1 more Smart Citation
“…The study found that the prevalence of underweight was about 64%, and that the prevalence of underweight was 1.7 times higher in children of illiterate women. 18 The present study also supports previous studies that maternal educational status is a very important determinant for nutritional status of children.…”
Section: Factors Associated With Underweightsupporting
confidence: 92%
“…18 The present study shows that birth weight influences the nutritional status of preschool children and that low birth weight is associated with underweight in preschool children. The study done by Bhutta and Salam reports that the risk factors for under-nutrition include low birth weight, inadequate breastfeeding, improper complementary feeding, and recurrent infections.…”
Section: Factors Associated With Underweightmentioning
confidence: 49%
“…The latter explanation may be particularly relevant to the city of Chicago, where strict public health measures, including mandatory quarantines, school closings, and bans on public gatherings, are believed to have significantly reduced the size of the pandemic (34). Underlying health conditions, like chronic obstructive pulmonary disease, tuberculosis, and malnutrition, are known to have a strong social gradient and likely associated with census tracts with lower literacy rates (14,16). Our findings that illiteracy is significantly and positively associated with ward-level allcause mortality and incidence of several other infectious diseases in the years before the pandemic speak to the probable lower underlying health status of census tracts with higher illiteracy rates.…”
Section: Discussionmentioning
confidence: 99%
“…Although there is evidence of substantial geographic variation in mortality rates across countries (2) and even within cities (3), studies of the 1918 pandemic in the United States (4,5), the United Kingdom (6, 7), Europe (8), South America (9-11), and Asia (12,13) focus mainly on differences in onset of the pandemic, age-specific mortality, and transmission of the virus across large geographic regions. Few studies have explored the effects of sociodemographic factors on differential mortality during the 1918 pandemic, despite the known impacts of social inequalities on disease progression and outcomes through decreased access to healthcare, overcrowding, comorbidities associated with lower resources, lower nutritional status, and a poor understanding of control measures because of lack of education (14)(15)(16)(17). One such study found that excess mortality from 1918 to 1920 was negatively associated with per-head income in many countries (2).…”
mentioning
confidence: 99%
“…Another study, conducted in 2014 in Karnataka [4], about the nutritional status of under-five tribal children concluded that the prevalence of underweight, stunting and wasting was 60.4 %, 55.4% and 43% respectively. Similar study conducted in Maharashtra in 2012 found out that the prevalence of underweight, stunting and wasting was 64, 61 and 29%, respectively and the risk of underweight was 1.7 times higher among children of illiterate mothers and those suffering from morbidities [5].…”
Section: Discussionmentioning
confidence: 52%